Incidence of Hepatitis C Virus Infection among Students in Public Tertiary Institution in North-Central Nigeria - Bello, Shakirat Iyabo; Erah, Patrick Omonua (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Hepatitis C Virus (HCV) disease is one of the principal health burden in the developing countries especially sub-Saharan Africa. Prevalence rates of 4.3-20% have been reported in various parts of Nigeria. The main objective of this study was to determine the incidence of HCV infection among students in the North-Central Nigeria with the view to identifying risk behavioral factors associated with the incidence. The sera from each of the 202 students enrolled in the study were tested for the presence of anti-HCV using a rapid visual immunoassay kit. A pre-tested questionnaire was used to obtain information on demographic characteristics and risk factors for the virus infection from the studied subjects. Informed consent was sought from the students and ethical approval granted by the institution. The students (mean age: 18.21± 3.57 years; age range: 17–48 years; and mainly females: 57.4%) had HCV incidence rate of 1.98%. Male has a lower risk of being infected with HCV than female counterparts (1:3). There was no significant association between socio-demographic characteristics and HCV positivity. Of all the behavioral risk factors, only those with tattoo showed significant association with HCV (p < 0.009). It is concluded that the incidence of HCV in the study area was low and the use of body tattoo is a major risk factor.